Implementation of Restorative Justice Principles in Indonesia: A Review - Eva Achjani Zulfa (GoAcademica Research & Publishing, 2020)
Restorative justice is a phrase that is very popular among law enforcers understood in various dimensions. Simple questions about restorative justice whether a